EU Accession and Determinants of Foreign Direct Investment Inflow: The Case of Turkey - Aygul, Esen (2016)
The world economy has changed since the decade due to its globalization. The majority of studies have analysed and discussed the effects of European Union (EU) accession in Turkey on foreign direct investment (FDI) inflows. Based on, this dissertation attempts to build empirical models to identify the determinants of foreign direct investment inflows in Turkey and to understand the effects of European Union accessions from the period of 1995-2015. Furthermore, this study examines FDI between the nine members of EU and Turkey. Panel data were collected for the Central and East European countries (CEEC): Bulgaria, Croatia, Estonia, Hungary, Latvia, Lithuania, Slovakia, Slovenia, Romania and Turkey. In order to analyse this topic, three different regression models were compared: Random Effects model (REM), fixed Effects model (FEM), and Pooled Ordinary Least Squares (POLS). According to econometric tests, REM was found the most appropriate model for this study. The results state that the host country macroeconomic variables of Turkey’s including market size, trade openness, inflation, negotiations and labour force are significant determinants of FDI inflow by the CEEC during the process of EU accession. It is also found that EU enlargement affects FDI inflow in the host country positively. Finally, the limitations and recommended future studies are presented.